Psychological Resilience and Self- efficacy for High school female students in Al qurayyat Province in the Kingdom of Saudi Arabia - Hamad, Muneera Mohamed (Journal of Educational and Psychological Sciences, 2020)
The present study aims to identify the relationship between, Psychological resilience .and self- efficacy. among the female students of the high school in Alqurayyat province in the Kingdom of Saudi Arabi. It also seeks to point out the level of Psychological resilience and self- efficacy among female students and indicate the extent to which Psychological resilience can be predicted through self- efficacy. Descriptive method was adopted by the researcher to achieve the objectives of the present research. Stratified random sampling technique was applied to select a sample of (164) female students. Data was collected by the following scales: Psychological resilience Scale prepared by (Shagora2012) and Self- efficacy Scale by the researcher. The results indicated that Psychological resilience and self- efficacy. levels are average among the High school female. students. The study also showed a statistically significant correlation between Psychological resilience and self- efficacy at the level of (0.01). The Psychological resilience of the study sample could be predicted through the degrees of self- efficacy. Based upon these results The study recommends., preparing counseling programs that help in developing psychological resilience and self- efficacy among high school students.